Implementasi Algoritma Hash Sha-256 untuk Validasi Integritas Artikel Jurnal Ilmiah Berbasis File PDF - Prasetya, Febri Adi Prasetya; Ardhianto, Eka (Jurnal Teknik Informatika dan Elektro, 2026)
The management of scientific journal articles in digital format has become a primary need in academic institutions. However, there is still a lack of automated systems capable of ensuring the authenticity and integrity of scholarly manuscripts, particularly in PDF format. This vulnerability opens up the potential for document manipulation or misuse, highlighting the need for a reliable and efficient digital validation solution. This study aims to develop a file integrity validation system for PDF journal articles using the Secure Hash Algorithm 256-bit (SHA-256). SHA-256 was selected due to its cryptographic strengths, including its ability to generate unique digital representations that are highly sensitive to content changes and resistant to collisions. The system is implemented as a web-based application using PHP as the server-side language and HTML for the user interface, allowing users to upload PDF files and automatically generate corresponding hash values. This research adopts a software engineering approach with experimental testing. System evaluation is conducted through two main scenarios: unmodified original files and files with minimal modifications. Performance metrics used include Integrity Verification Rate (IVR) and Tamper Detection Accuracy (TDA). Experimental results show that the system successfully verified all original files (IVR = 100%) and accurately detected all modified files (TDA = 100%) without any false positives or false negatives. These results indicate that the system can effectively validate document integrity with high accuracy. The proposed solution demonstrates significant potential for integration into digital journal management platforms such as Open Journal Systems (OJS), thereby contributing to the security and trustworthiness of digital scholarly publishing.